Improving weekend review for trauma and elective orthopaedic patients in the post-operative period. Issue 4 (7th August 2018) - Khoury, Alexandra; Jones, Mark; Buckle, Christopher; Williamson, Mark; Slater, Guy
Abstract : Purpose: Weekend surgery carries higher mortality than weekday surgery, with complications most commonly arising within the first 48 hours. There is a reduced ability to identify complications at the weekend, with early signs going undetected in the absence of thorough early patient review, particularly in the elderly with multiple co-morbidities. Weekend working practices vary amongst UK hospitals and specialties. The weekend effect has been a prominent feature in the literature over the past decade. The purpose of this paper is to identify the number of patients undergoing weekend surgery who receive a Day 1 post-operative review and improve this outcome by implementing an effective change. Design/methodology/approach: It was observed that not all patients undergoing surgery on a Friday or Saturday at the authors' District General Hospital were receiving Day 1 post-operative review by a clinician. A retrospective audit was carried out to identify percentage of patients reviewed on post-operative Day 1 at the weekend. A change in handover practice was implemented before re-audit. Findings: In Phase 1, 54 per cent of patients received Day 1 post-operative reviews at the weekend against a set standard of 100 per cent. A simple change to handover practice was implemented to improve patient safety in the immediate post-operative period resulting in 96 per cent of patients reviewed on Day 1 post-operatively at re-audit. Originality/value: This study confirms that simple changes in handover practices can produce effective and translatable improvements to weekend working. This further contributes to the body of literature that acknowledges the existence of a weekend effect, but aims to evolve weekend working practices to accommodate improvement within current staffing and resource availability by maximising efficiency and communication.